Ekstrak Bawang Dayak Penghambat Pertumbuhan Escherichia coli dan Staphylococcus aureus pada Daging Ayam - Taufikkilah Romadhon; Winiati Pudji Rahayu; Harsi Dewantari Kusumanigrum (Jurnal Ilmu Pertanian Indonesia, 2023)
Microbial contamination on chicken meat can be inhibited by applying natural antimicrobials. Dayak onions (Eleutherine palmifolia (L.) Merr.) are reported to inhibit the growth of Escherichia coli and Staphylococcus aureus. This study aims to confirm and apply dayak onion extract (EBD) as an antimicrobial in fresh chicken meat. The observation parameters were the microbiological quality and physical properties of chicken meat after inoculation with E. coli and S. aureus and dipped in EBD solution with concentrations of 0, 3.0, 9.0, and 15.0 mg/mL for E. coli, and 0, 2.5, 7.5, and 12.5 mg/mL for S. aureus. The results showed that EBD-70% ethanol showed better bacterial inhibition than EBD-96% ethanol. Inhibition for both microbes can be achieved by concentrations of 3.0 and 2.5 mg/mL EBD, as visually observed in liquid media. Concentrations of 15.0 and 12.5 mg/mL showed significant results in reducing the total microbes of both types in chicken meat after 12 hours of room temperature storage (28±2°C) and 9 days of refrigerator storage (5±1°C). A combined application of 15.0 and 12.5 mg/mL EBD and refrigerator temperature can be recommended to reduce total E. coli and S. aureus and maintain the Aw and pH of the chicken meat. Keywords: antimicrobial, chicken meat, dayak onion extract, Escherichia coli, Staphylococcus aureus